HUBUNGAN TINGKAT KEPATUHAN MINUM OBAT DENGAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI KELOMPOK PENGELOLAAN PENYAKIT KRONIS (PROLANIS) KLINIK QITA - Ferry Effendi; Elis Tiahesara; Debi Rizki Azana (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2018)
Hypertension is widely known for its cardiovascular disease in which sufferers have blood pressure above normal blood pressure, precisely where systolic blood pressure ≥ 140 mmHg and diastolic pressure ≥ 90 mmHg measured in calm at two measurements. Compliance to medication of hypertension contributes greatly to the stability of the blood pressure. One of the efforts made to improve compliance with medication of hypertension with the chronic disease management program (Prolanis). This research aims to know the relationship of the level of compliance of taking the drug with blood pressure in patients of hypertension in chronic disease management group (Prolanis) Qita Clinic. This research use analytic research method to approach cross-sectional, in the study sample is determined by the method of purposive. This research instrument is the questionnaire MMAS-8 (Morisky Medication Adherence Scale-8) and 1 set of tools tensimeter. From the results of the research showed that respondents with high compliance as much as 14 respondents (46.7%), compliance are as many as 5 respondents (15.7%) and low compliance as much as 11 respondents (36.7%). Correlation of test results of these studies showed a relationship with medication compliance systolic blood pressure with a p value of 0.05 signifies < 0.038 and there is a connection with diastolic blood pressure with a p value of 0.05 signifies < 0.024.